ANALISIS KANDUNGAN SULFORAFAN PADA FASE KECAMBAH BEBERAPA JENIS BROKOLI DALAM MEDIA MS YANG DIBERIKAN NAA DAN BAP SECARA IN VITRO - Lengkong, Edy F.; Tilaar, Wenny; Pinaria, Arthur (Sam Ratulangi University, 2022)
This study aims to: (1) determine the content of sulforaphane in several types of broccoli sprouts. (2) Knowing the difference in sulforaphane content in the combination of NAA, BAP and types of broccoli grown on MS media; (3) knowing the difference in sulforaphane content in the combination of NAA and types of broccoli sprouts grown on MS media; (4) knowing the difference in sulforaphane content in the combination of BAP and the type of broccoli sprouts grown on MS media. This study used a completely randomized design (CRD) arranged in a factorial manner, namely factor A: NAA 0, 0,5, and 1 ppm. B: BAP 0, 1, 2 ppm and C : 2 Types of Broccoli. The variables observed were: germination time, germination weight, and sulforaphane content. The data were analyzed by analysis of variance and continued with the 5% BNT test. The results showed that germination time began to appear on day 3 and all seeds germinated. Sprout weight varied greatly, and the combination of treatments N1, B0 and BR2 gave the highest average weight and calculated concentration (ENT) of sulforaphane, followed by treatments N0B2BR2 and N0,5B0BR1.